Defining the suitable adjacent microgrids to form a temporary system of coupled microgrids - Shahnia, Farhad; Arefi, A. (2017)
© 2016 IEEE.Majority of the remote areas have self-sufficient and isolate electricity systems. These systems are preferred to generate the majority of the electricity from renewable energy resources if they are available in the area to reduce the cost of electricity production. Thereby, they can be assumed as sustainable islanded microgrids. Large remote areas may be supplied by multiple adjacent microgrids, each with a different operator. The adjacent microgrids may couple and exchange power temporarily to support each other under emergencies such as overloading, generation shortfalls, or faults. Defining the suitable nearby microgrid(s) to be coupled is a challenging task. This paper uses a heuristic-based optimization approach to evaluate the suitability of the connection of nearby microgrids and the minimum technical impacts on the newly generated system. The impact of the developed approach is assessed by MATLAB-based numerical analyses under a stochastic environment.